Gerakan Dakwah Komunitas Hijrah pada Kaum Muda di Banten: Kaderisasi, Agensi, dan Otorisasi - Umdatul Hasanah; Fahma Islami (Jurnal Komunikasi Islam, 2023)
This article reports on research conducted with leaders, ustadz, and adherents of those hijrah communities, using qualitative research through participatory observations and in-depth interviews. This study focuses on the examination of what extent the hijrah community in Banten has the potential to create the authority of da'wah (religion) shift, especially for millennial Muslims. Findings have revealed that indeed the hijrah community has become a potential new space for the formation of new religious authorities. It is found from several indicators; first, there has been the institutional transformation from informal religious movement to formal and legal one. Second, these hijrah communities strengthen agents and networks of institutions. Third, strengthening cadre formation and formalizing the curriculum. Fourth, strengthening institutional existence and influence by expanding the distribution of coaching and segmentation.